Crimes and Punishments, in Compiled and Revised Laws of the Territory of Idaho 354 (M. Kelly, Territorial Printer 1875), § 133. - (:unkn) unknown (General Publisher, 1875)
Prohibited the carrying of “any pistol, gun, knife, dirk, bludgeon, or other offensive weapon, with intent to assault any person.” Punishable by imprisonment for up to 3 months or a fine up to $100.
--
Keywords: CARRY - INTENT TO COMMIT CRIME